THE RELATIONSHIP BETWEEN TIME MANAGEMENT AND SELF-CONTROL WITH ACADEMIC PROCRASTINATION IN STUDENTS OF MITRA SEHAT MANDIRI VOCATIONAL HIGH SCHOOL SIDOARJO - Althafani, Brillianti Dwigta; Nastiti, Dwi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: Academic procrastination is a tendency or common habit of delaying to start and complete the implementation of necessary tasks, in order to achieve certain goals. The phenomenon found is that there are still students with a high level of academic procrastination. The purpose of this study was to determine the relationship between time management and self-control and academic procrastination in vocational high school students. Method: This research method uses a quantitative approach with a correlational design. The research population was 340 students with 172 students as samples. The sampling technique used is stratified random proportional sampling. The data collection technique used a time management scale with a reliability value of 0.886, a self-control scale with a reliability value of 0.831 and a procrastination scale with a reliability value of 0.892 with a Likert scale model. The data analysis technique uses multiple correlation with the JASP program. Results: The results of this study showed an F value of 448.991 (p = < 0.001 < 0.05) which means that time management and simultaneous self-control have a significant relationship with academic procrastination. The results of Pearson's correlation analysis showed that there was a significant negative relationship between time management and academic procrastination (r = -0.520), with a p-value of < 0.001 (< 0.05), and there was a significant negative relationship between self-control and academic procrastination (r = -0.739), with a p-value of < 0.001 (< 0.05). Novelty: This study highlights the simultaneous influence of time management and self-control on academic procrastination among vocational high school students, providing insights into behavioral aspects that have not been extensively explored in this specific student group.